Heat Perception and Aversive Learning in Honey Bees: Putative Involvement of the Thermal/Chemical Sensor AmHsTRPA - Junca, Pierre; Sandoz, Jean-Christophe (Frontiers in Physiology, 2015)
The recent development of the olfactory conditioning of the sting extension response (SER) has provided new insights into the mechanisms of aversive learning in honeybees. However, until now, very little information has been obtained concerning US detection and perception in this aversive conditioning. In the initial version of SER conditioning, bees learned to associate an odor CS with an electric shock US. Recently, we proposed a modified version of SER conditioning, in which thermal stimulation with a heated probe is used as US. This procedure has the advantage of allowing topical US applications virtually everywhere on the honeybee body. In this study, we made use of this possibility and mapped thermal responsiveness on the honeybee body, by measuring workers' SER after applying heat on 41 different structures. We then show that bees can learn the CS-US association even when the heat US is applied on body structures that are not prominent sensory organs, here the vertex (back of the head) and the ventral abdomen. Next, we used a neuropharmalogical approach to evaluate the potential role of a recently described Transient Receptor Potential (TRP) channel, HsTRPA, on peripheral heat detection by bees. First, we applied HsTRPA activators